Instructional Leadership of School Principals in Enhancing Teachers’ Digital Literacy Competencies at Public Junior High Schools in Sungai Batang District - Andi Kumala Shari; Lia Yuliana (FKIP - Universitas Riau, 2026)
The novelty of this study lies in its exploration of instructional leadership practices for strengthening digital literacy in schools facing limited ICT infrastructure, unstable internet access, and diverse levels of teacher digital competence. A descriptive qualitative approach was employed using interviews, observations, and document analysis. The study involved 15 informants consisting of 3 principals, 3 vice principals, and 9 teachers selected through purposive sampling based on their direct involvement in instructional leadership practices and digital learning implementation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. The findings revealed that principals promoted teachers’ digital literacy through digital platform policies, professional training, mentoring, motivation, and instructional supervision. Nevertheless, implementation remained uneven due to varying teacher competencies, basic-level training, limited continuous mentoring, and inadequate ICT facilities. The study concludes that effective instructional leadership in digital transformation requires sustained professional development, peer mentoring, evidence-based supervision, and equitable access to digital resources, thereby extending the understanding of instructional leadership in resource-constrained school contexts.